Urban expansion and mobility: a case study in Patos - PB (Research, Society and Development, 2022)
In recent decades, Brazilian cities have grown in an uncontrolled and disorderly way, a process that associated with the lack of urban mobility is responsible for the generation of problems that cause negative impacts on the quality of life of the population. Thus, taking into account the importance of the correlation between urban sprawl and mobility, integrated urban planning is an alternative that can be used to solve existing urban problems and prevent others from arising. Therefore, the objective of this study is to investigate the relationship between these processes in a city located in the sertão of Paraiba, through the evaluation of its urban mobility, using the Sustainable Urban Mobility Index (I_SUM) and the survey of information about how its urban growth occurred. Thus, the urban growth of Patos favored displacements that take place by means of individual vehicles, considering that there were no incentives for the population to use non-motorized and collective modes of transportation. The results show that the index obtained can collaborate in the development of relevant diagnoses. The I_SUM calculated for the city that is the object of this study can be used as an instrument capable of guiding the creation of public policies based on the promotion of urban mobility, as the city grows, in order to harmonize these two issues of urban development.